Investment in Brazil : From Crisis to Recovery - Krznar, Ivo (IMF Working Papers; Working Paper, 2018)
While Brazil's deep recession has been broad based, it has been marked by a particularly large fall in investment. Real investment fell by around 30 percent between the beginning of 2014 and the beginning of 2017. This paper finds that a variety of factors contributed to the investment decline, including a deterioration in Brazil's medium-term growth prospects, rising real interest rates, falling terms of trade, rising uncertainty related to economic policy, rising levels of corporate leverage and lower cash flow. Some of the factors that have weighed on investment over recent years have begun to normalize providing some impetus for a recovery. However, still-high levels of corporate leverage and the prospect of continued uncertainty related to economic policy settings suggest a turnaround in investment is likely to be subdued.